2010
DOI: 10.1179/106698110x12804993427126
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effects of a thoracic spine thrust manipulation on the autonomic nervous system: a randomized clinical trial

Abstract: Thoracic spine manipulation has been shown to be effective for the management of neck pain. The purpose of this study was to investigate the immediate effect of a T3-T4 spinal thrust manipulation on autonomic nervous system activity in subjects with chronic cervical pain. An additional aim was to determine if the manipulation resulted in an immediate pain relief in patients with chronic neck pain when compared to a placebo intervention. One hundred subjects with chronic neck pain were randomly assigned to rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 100 publications
1
46
1
Order By: Relevance
“…Thoracic manipulation can be performed without significant movement of the head or skull and thus allows for reliable pretest and posttest imaging without motion artifacts confounding the data. Second, manual therapy to the thoracic spine may also induce sympathoexcitatory effects beyond segmental distribution, 32,58,62 giving rise to the notion that pain reduction [ research report ] associated with manipulation may not be segmentally specific. Finally, this project aimed to establish a testing protocol and to identify cerebral structures that may be associated with hypoalgesia following thrust manipulation to the thoracic spine by incorporating noxious stimuli in tandem with functional imaging premanipulation and postmanipulation.…”
Section: Limitationsmentioning
confidence: 99%
“…Thoracic manipulation can be performed without significant movement of the head or skull and thus allows for reliable pretest and posttest imaging without motion artifacts confounding the data. Second, manual therapy to the thoracic spine may also induce sympathoexcitatory effects beyond segmental distribution, 32,58,62 giving rise to the notion that pain reduction [ research report ] associated with manipulation may not be segmentally specific. Finally, this project aimed to establish a testing protocol and to identify cerebral structures that may be associated with hypoalgesia following thrust manipulation to the thoracic spine by incorporating noxious stimuli in tandem with functional imaging premanipulation and postmanipulation.…”
Section: Limitationsmentioning
confidence: 99%
“…1 It is thought that approximately 50-70% of individuals will experience neck pain at least once during their lifetime and up to 60% of patients continue to report chronic pain 5 years after onset of symptoms. [1][2][3] There is a tremendous economic burden associated with neck pain, resulting in increased visits to health care providers, missed work, and loss of productivity, and it is responsible for the second highest annual workers' compensation costs in the United States. 1,[4][5][6] A common classification of neck pain is mechanical neck pain.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] There is a tremendous economic burden associated with neck pain, resulting in increased visits to health care providers, missed work, and loss of productivity, and it is responsible for the second highest annual workers' compensation costs in the United States. 1,[4][5][6] A common classification of neck pain is mechanical neck pain. 7 Although the definition varies among different research studies, mechanical neck pain is most commonly defined as pain located in the cervical spine or cervicothoracic junction that is elicited and/or exacerbated by cervical motion and/ or palpation of cervical musculature.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously described in detail the standardized approach to identify the T3-T4 segment. 52 During the pupil measurements, all subjects were supine with the knees slightly flexed over a bolster and with the head, with the goggles in place, on a pillow maintaining a neutral cervical spine position. The goggles created a complete darkness for the subjects, allowing for a constant maximum pupil diameter during the pupil measurement.…”
Section: Study Protocolmentioning
confidence: 99%
“…We have previously reported that, within a group of chronic neck pain patients, no immediate reduction of pain was achieved following an upper thoracic thrust manipulation; nor was an overall change in sympathetic functioning demonstrated compared with a sham intervention group. 52 Within that study, the presence of audible sounds was not considered as a factor, which could have influenced the study results. The effects of audible sounds on pain perception and neurophysiological mechanisms (specifically the autonomic nervous system) following thrust manipulation have not been demonstrated at this time.…”
mentioning
confidence: 98%